2015
DOI: 10.1016/j.bone.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate chemotherapy triggers touch-evoked pain and increased CGRP-positive sensory fibres in the tibial periosteum of young rats

Abstract: Although bone pain caused by cancer chemotherapy is a well-recognized and significant problem, with approximately 1 in 10 childhood cancer patients being reported to experience isolated bone pain along with other skeletal complications, the underlying mechanisms are poorly understood and there is no specific treatment. In this study, effects of methotrexate (MTX) treatment on pain in the hind legs and the extent of sensory innervation of the tibial bone were examined through a 20-day time course in young rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, the involvement of miR‐344g in spinal cord development and pain mechanisms has been previously investigated (Soula et al, 2018). Subcutaneous injections of MTX are known to be in line with a mild amount of pain (Bechard et al, 2014; Zhou et al, 2015). The upregulated miR‐344g observed on Day 3 might be because of subcutaneous injections with MTX, resulting in pain in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the involvement of miR‐344g in spinal cord development and pain mechanisms has been previously investigated (Soula et al, 2018). Subcutaneous injections of MTX are known to be in line with a mild amount of pain (Bechard et al, 2014; Zhou et al, 2015). The upregulated miR‐344g observed on Day 3 might be because of subcutaneous injections with MTX, resulting in pain in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified that RAMP1 is specifically expressed in hematopoietic progenitor cells, which led us to speculate that CGRP might be a specific ligand for CRLR in hematopoietic cells. CGRP is a neuropathic peptide that is primarily secreted from sensory nerves after stimulation of transient receptor potential vanilloid receptor-1 (TRPV1), which is distributed in C fibers and upstream, with mechanical stimulation, infection, ischemia, and pain 2830 . Binding of CGRP to the CRLR/RAMP1 receptor activates adenylate cyclase, which elevates intracellular cAMP and activates protein kinase A (PKA), leading to phosphorylation of multiple targets, such as potassium-sensitive ATP channels, extracellular signal-related kinases (ERKs), and cAMP response element-binding protein (CREB) 28 .…”
Section: Introductionmentioning
confidence: 99%